I’m still learning. A web platform for the intervention in reading disabilities (2020)
In 2014, 20% of the 4th graders had an unsatisfactory evaluation in the national exam of Portuguese language. This percentage is similar in the 6th and 9th grades indicating that a large number of Portuguese students have reading difficulties. The e-learning platform “I’m still learning” was developed to provide a systematic intervention with students (from 1st to 4th grade) experiencing reading difficulties. This free access platform provides a set of didactic sequences to promote phonological awareness, word reading, reading fluency and comprehension. Informal tasks for reading assessment are also included. In this paper we describe the platform and the theoretical framework adopted in its construction.